Targeting Autophagy in Cancer Therapy - Yang, Jin-Ming (Current Cancer Research, 2016)
This volume will detail the current state and perspectives of autophagy-based cancer therapy. Covering a wide range of topics, it will include an overview of autophagy as a therapeutic target in cancer, autophagy modulators as cancer therapeutic agents, implications of micro-RNA-regulated autophagy in cancer therapy, modulation of autophagy through targeting PI3 kinase in cancer therapy, targeting autophagy in cancer stem cells, and roles of autophagy in cancer immunotherapy. In addition, the volume will review applications of system biology and bioinformatics approaches to discovering cancer therapeutic targets in the autophagy regulatory network. The volume will be beneficial for a variety of basic and clinical scientists, including cancer biologists, autophagy researchers, pharmacologists, and clinical oncologists who wish to delve more deeply into this field of cancer research. This volume will be the first book to focus solely on autophagy as a target in cancer therapy. As well, it will comprehensively discuss the roles of autophagy in most currently available cancer treatments.